A expressividade enunciativa do adjetivo no gênero textual redações de vestibular - Ribeiro, Simone Beatriz Cordeiro (2010)
This work was done in order to verify the expressiveness of the adjective set the textual genre writing exam, proof of Writing Contest Vestibular/2008 from Unioeste. As the practice of teaching of text types has been much discussed, as well as teaching practical language together with the text, we chose to work which focused on the union of these two poles that were and still are worked in a decontextualized classes in Portuguese. According to the theoretical discussion developed over the course of the text, it was observed that the use of language is entirely linked to discursive contexts. Therefore, since this study is the adjective, we attempted to verify its expression in three modes of interpretation: Position Available with change of direction, position and compulsory free position without changing the meaning, based on the theoretical assumption of Callou and Serra (2003b), Neves (2000), Mira Mateus ec. al. (1983), Barros (1985), among other scholars. According to the literature investigated, it can be said that the use of the adjective in front castle or proposed positions is not just to use syntactic or semantic, is also interconnected discursive intentions of their users and suffers constant influence of the genre in which text is inserted. Therefore, it is expected that the content covered in this study will help teachers of Portuguese in class writing in the classroom, contributing to the knowledge of text types and purpose in education. As well, helping the students in the process of identification and production of gender, and language acquisition. This focused approach to education is justified as a result of this work being in the Search Language Linguistic Practice Line, Cultural and Education.